Galen on the properties of foodstuffs = De alimentorum facultatibus - Galen (Cambridge University Press, 2003)
This work lucidly describes the ways in which foods were thought to affect the body and were in turn affected by it, and contains revealing snippets of social comment. This book provides a full translation together with the first ever detailed introduction, commentary and discussion of terminology.